2007
DOI: 10.1111/j.1365-2141.2007.06663.x
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin generation: the functional role of alpha‐2‐macroglobulin and influence of developmental haemostasis

Abstract: SummaryCurrently available chromogenic and fluorogenic substrates for endogenous thrombin potential (ETP) measurement are cleaved by both free (active) and alpha-2-macroglobulin-bound (inactive) thrombin, leading to an overestimation of ETP. Commercial methods for ETP measurement determine this using a mathematical algorithm, which assumes the contribution of alpha-2-macroglobulin to the ETP. This limits application of such methods to populations where variation in alpha-2-macroglobulin concentrations is obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 10 publications
(11 reference statements)
0
34
0
Order By: Relevance
“…In addition, one of the most devastating arterial thrombi in children with CHD is the complete occlusion of a systemic to pulmonary artery shunt, which is fatal unless immediately relieved. Concerning venous thrombi, although epidemiologic studies have demonstrated that infants and children have decreased venous thrombosis compared with adults, [168][169][170] which is a result of unique protective mechanisms (increased α 2 -macroglobulin, 171 decreased thrombin generation, and altered vessel wall properties [10][11][12]168,172,173 ), children with CHD have increased risk for developing thrombosis (section 4.1). In addition to the development of pulmonary emboli, patients with CHD are at risk for other life-threatening venous thrombi.…”
Section: Consequences Of Thrombosis In Patients With Chdmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, one of the most devastating arterial thrombi in children with CHD is the complete occlusion of a systemic to pulmonary artery shunt, which is fatal unless immediately relieved. Concerning venous thrombi, although epidemiologic studies have demonstrated that infants and children have decreased venous thrombosis compared with adults, [168][169][170] which is a result of unique protective mechanisms (increased α 2 -macroglobulin, 171 decreased thrombin generation, and altered vessel wall properties [10][11][12]168,172,173 ), children with CHD have increased risk for developing thrombosis (section 4.1). In addition to the development of pulmonary emboli, patients with CHD are at risk for other life-threatening venous thrombi.…”
Section: Consequences Of Thrombosis In Patients With Chdmentioning
confidence: 99%
“…Retrospective autopsy studies in children have indicated an incidence of PE at autopsy of 0.73% to 3.7%, depending on the population studied. 225,226 The incidence of PE in children is less than in adults and may be related to unique protective mechanisms, including decreased thrombin generation, increased levels of the inhibitor of coagulation α 2 -macroglobulin, and enhanced antithrombotic potential of the vessel wall 12,13,[168][169][170][171][172] (section 2.5, Developmental Hemostasis).…”
Section: Pe In Chdmentioning
confidence: 99%
“…Studies of developmental haemostasis have documented increased levels of alpha-2-macroglobulin throughout infancy and childhood compared with adults [21]. The relative contribution of alpha-2-macroglobulin bound to and inhibiting thrombin is significant and has been reported to vary from 16 to 64% across the paediatric age range, while being approximately 7% in adults [22]. This inactive thrombin complex has to be taken into account in interpretation of the results of thrombin generation to prevent overestimation in children.…”
Section: Discussionmentioning
confidence: 97%
“…As pointed out by Ignjatovic et al [20], one has to be careful when comparing thrombin generation of neonates and adults using fluorescent substrates, as the two study groups differ in their content of alpha2-macroglobulin (a2-MG) and a-2MG-bound thrombin, although physiologically inactive, still has amidolytic activity toward the used substrate. However, in calibrated automated thrombography, the fraction of a2-MG-bound thrombin is estimated on the basis of the remaining amidolytic activity after all the free thrombin has been inhibited [21].…”
Section: Discussionmentioning
confidence: 99%